The miR-124-Prolyl Hydroxylase P4HA1-MMP1 axis plays a critical role in prostate cancer progression - Chakravarthi, Balabhadrapatruni V. S. K. (Impact Journals LLC, 2014)
Collagen prolyl hydroxylases (C-P4HAs) are a family of enzymes involved in collagen biogenesis. One of the isoforms of P4HA, Prolyl 4-hydroxylase, alpha polypeptide I (P4HA1), catalyzes the formation of 4-hydroxyproline that is essential for the proper three-dimensional folding of newly synthesized procollagen chains. Here, we show the overexpression of P4HA1 in aggressive prostate cancer. Immunohistochemical analysis using tissue microarray demonstrated that P4HA1 expression was correlated with prostate cancer progression. Using in vitro studies, we showed that P4HA1 plays a critical role in prostate cancer cell growth and tumor progression. Expression profiling studies using P4HA1-modulated prostate cells suggested regulation of Matrix metalloprotease 1. The invasive properties of P4HA1 overexpressing cells were reversed by blocking MMP1. Our studies indicate P4HA1 copy number gain in a subset of metastatic prostate tumors and its expression is also regulated by microRNA-124. MiR-124 in turn is negatively regulated by transcriptional repressors EZH2 and CtBP1, both of which are overexpressed in aggressive prostate cancer. Chick chorioallantoic membrane (CAM) assay and mice xenograft investigations show that P4HA1 is required for tumor growth and metastasis in vivo. Our observations suggest that P4HA1 plays a critical role in prostate cancer progression and could serve as a viable therapeutic target.